2018
DOI: 10.3390/ijerph15081704
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Environmental and Occupational Particulate Air Pollution as a Potential Contributor to Neurodegeneration and Diabetes: A Systematic Review of Epidemiological Research

Abstract: It has been hypothesised that environmental air pollution, especially airborne particles, is a risk factor for type 2 diabetes mellitus (T2DM) and neurodegenerative conditions. However, epidemiological evidence is inconsistent and has not been previously evaluated as part of a systematic review. Our objectives were to carry out a systematic review of the epidemiological evidence on the association between long-term exposure to ambient air pollution and T2DM and neurodegenerative diseases in adults and to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 135 publications
(320 reference statements)
1
30
0
Order By: Relevance
“…dementia, cognitive impairment) and metabolic (e.g. diabetes) diseases and that PM can cause reproductive and developmental toxicity [12,[16][17][18][19][20][21][22] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…dementia, cognitive impairment) and metabolic (e.g. diabetes) diseases and that PM can cause reproductive and developmental toxicity [12,[16][17][18][19][20][21][22] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…They produce many biological effects on wildlife and humans, including immunological, mutagenic, and reproductive alterations ( Yu et al, 2011 ). A continuous increase in chronic and infectious diseases associated with contaminant exposure has been observed in recent decades ( DeSantis et al, 2019 ; Dimakakou et al, 2018 ; Liu et al, 2019 ). A relationship between pollutants and viral diseases (such as COVID-19) was recently reported ( Tsatsakis et al, 2020 ).…”
Section: Pollutants and Their Relationship To Covid-19mentioning
confidence: 99%
“…Exposure for a long period of time to ultrafine particles in areas near highways has been associated with stroke, ischemic heart disease, hypertension, and type 2 diabetes (17,18). Robust data highlighted the association between long-term exposure to air pollution and type 2 diabetes and neurodegenerative disorders in adults, such as dementia and a general decline in cognition (19). Another recent study identified the alteration of several metabolic pathways that mediate the development of asthma and cardiovascular diseases associated with ambient air pollutants (20).…”
Section: Introductionmentioning
confidence: 99%